A Study on Nomophobia - Mobile Phone Dependence, Among Students of a Medical College in Bangalore - Pavithra MB; Suwarna Madhukumar; Mahadeva Murthy TS (Medsci Publications, 2015)
Background: Smart phones today have become an important part of our techno-culture, especially among the younger population. Discomfort, anxiety, nervousness or anguish caused by being out of contact with a mobile phone is termed as "Nomophobia"- no mo- bile phobia. Nomophobia is on the rise across the globe. Objectives: To assess the prevalence of Nomophobia and mobile phone dependence among the students of a medical college. Material and Methods: A cross-sectional study was carried out in 200 students of a medical college in Bangalore. A pre-designed and pre-tested questionnaire was used to get information. Data ana- lyzed by using Statistical Package of Social Sciences (SPSS) 17.0. Results: The study population of 200 students comprised of 47.5% females and 52.5% males. Majority (74%) of the students spent Ru- pees 300-500 per month on mobile recharge. About 23% students felt they lose concentration and become stressed when they do not have their mobile around, 79(39.5%) students were Nomopobic in this study and another 27% were at risk of developing Nomopho- bia. Conclusion: The result of our study is indicative of increasing prevalence of Nomophobia among younger generation. Further re- search and multi-centric studies are required to investigate more in depth the psychological aspects and solutions for nomophobia.